Juvenile psammomatoid ossifying fibroma: An unusual case report - Nidhi Yadav; Prashant Gupta; Shantala R Naik; Ashish Aggarwal (Wolters Kluwer Medknow Publications, 2013)
Ossifying fibromas are well-demarcated benign fibro-osseous tumors of craniofacial skeleton most often in the jaws. It has two types, conventional and juvenile ossifying fibroma (JOF). JOF is considered a separate entity from ossifying fibroma due to its locally aggressive behavior and tendency to occur at a young age. Two subtypes of JOF, i.e., juvenile psammomatoid ossifying fibroma (JPOF) and juvenile trabecular ossifying fibroma have been identified on the basis of histology 70% of the JPOF occur in the paranasal sinuses, 20% in the maxilla and only 10% in the mandible. Here, we report a case of JPOF in a 14-year-old girl causing an asymptomatic expansile swelling in the right mandibular posterior region, which is a rare site for this tumor.